The Spatial and Temporal Variability of Air-Sea CO2 Fluxes and the Effect of Net Coral Reef Calcification in the Indonesian Seas: A Numerical Sensitivity Study - Mayer, Bernhard; Rixen, Tim; Pohlmann, Thomas (Frontiers in Marine Science, 2018)
A numerical model system was developed and applied to simulate air-sea fluxes of CO2 and coral reef calcification in the Indonesian Seas and adjacent ocean basin for the period 1960 to 2014 on a fine resolution grid (ca. 11 km) in order to study their response to rising sea water temperatures and CO2 concentrations in the atmosphere. Results were analyzed for different sub-regions on the Sunda Shelf (Gulf of Thailand, Malacca Strait, Java Sea) and show realistic and different levels, signs and pronounced temporal variability in air-sea CO2 flux. The Gulf of Thailand changes from an atmospheric CO2 sink during the boreal winter to a CO2 source in summer due to higher water temperatures, while other sub-regions as well as the entire averaged Sunda Shelf act as a continuous source of CO2 for the atmosphere. However, increasing atmospheric CO2 concentrations weakened this source function during the simulation period. In 2007, the model simulations showed even a first flux inversion, in course of which the Java Sea took up CO2 . The simulated trends suggest that the entire Sunda Shelf will turn into a permanent sink for atmospheric CO2 within the next 30 to 35 years if current trends remain constant. Considering the period between 2010 and 2014, coral reef calcification enhanced the average CO2 emission of the Sunda Shelf by more than 10 % from 15 to 17 Tg C yr−1 due to lowering the pH and increasing the partial pressure of CO2 in surface water. During the entire period of simulation, net reef calcification decreased although increasing seawater temperature mitigated effects of reduced CO2 emission and the resulting decrease of the pH values on reef calcification. Our realistic simulation results already without consideration of any biological processes suggest that biological processes taking up and releasing CO 2 are currently well balanced in these tropical regions. However, the counteracting effects of climate change on the reef calcification, on other biological processes and the carbonate system need to be investigated in more detail. SST ◦increased by about 0.6 C during the last 55 years, while SSS decreased by about 0.7 psu.